2015
DOI: 10.1167/iovs.15-17661
|View full text |Cite
|
Sign up to set email alerts
|

The Usefulness of Gaze Tracking as an Index of Visual Field Reliability in Glaucoma Patients

Abstract: High FL and FP rates tend to raise MD values. By contrast, high values of move(3-5), move(≥6), TFF, BF, and PSD tend to lower MD values. Thus, GT parameters can be used as new indices of VF reliability through the prediction of over- or underestimation of VF results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 17 publications
1
33
0
Order By: Relevance
“…[9, 10] The MP-3 microperimeter predefines retinal positions and is equipped with an auto-tracking system. As a result, a stimulus can be projected onto these predefined retinal positions mitigating the problem of eye movements during the VF measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9, 10] The MP-3 microperimeter predefines retinal positions and is equipped with an auto-tracking system. As a result, a stimulus can be projected onto these predefined retinal positions mitigating the problem of eye movements during the VF measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have recently reported that eye movements during the VF test are closely related to unreliable VF results and under-estimation of VF sensitivity. [9, 10]…”
Section: Introductionmentioning
confidence: 99%
“…In particular, fixation behavior exceeding 3° tended to have a lower mean deviation value [24] and was influenced by the structure-function relationship analysis [25]. In the current study, a weak significant correlation was demonstrated between fixation behavior and threshold variability expressed as RMSE for the Point and Cross targets.…”
Section: Discussionmentioning
confidence: 60%
“…The study of large number of glaucoma patients by Ishiyama et al [2426] reported that the gaze tracking waveform recorded by the HFA influenced the reliability of the results of visual field tests. In particular, fixation behavior exceeding 3° tended to have a lower mean deviation value [24] and was influenced by the structure-function relationship analysis [25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies [23,36] also found that image quality was lower in the glaucoma group than in the normal group. The reason for this is not clear and may be because glaucoma patients have decreased fixation stability [37,38] and their eye movements could affect image quality [23]. Moreover, when eyes had a +2.00D overcorrection, the internal fixation target became blurred and the fixation stability decreased further.…”
Section: Discussionmentioning
confidence: 99%